2001
DOI: 10.1038/35101607
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of a multiple drug resistant Salmonella enterica serovar Typhi CT18

Abstract: Salmonella enterica serovar Typhi (S. typhi) is the aetiological agent of typhoid fever, a serious invasive bacterial disease of humans with an annual global burden of approximately 16 million cases, leading to 600,000 fatalities. Many S. enterica serovars actively invade the mucosal surface of the intestine but are normally contained in healthy individuals by the local immune defence mechanisms. However, S. typhi has evolved the ability to spread to the deeper tissues of humans, including liver, spleen and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
1,067
1
11

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,171 publications
(1,110 citation statements)
references
References 28 publications
23
1,067
1
11
Order By: Relevance
“…This is in line with other genomes of enteric bacteria sequenced so far which feature a single chromosome with 4.3-5.0 Mb in length (7)(8)(9)(10). A comparison of S. typhi isolates from around the world indicate that they are highly related and that they emerged from a single point of origin approximately 30,000 to 50,000 years ago (11).…”
Section: Molecular and Biologic Features Of Salmonella Typhisupporting
confidence: 83%
“…This is in line with other genomes of enteric bacteria sequenced so far which feature a single chromosome with 4.3-5.0 Mb in length (7)(8)(9)(10). A comparison of S. typhi isolates from around the world indicate that they are highly related and that they emerged from a single point of origin approximately 30,000 to 50,000 years ago (11).…”
Section: Molecular and Biologic Features Of Salmonella Typhisupporting
confidence: 83%
“…The complete ~5 Mb genome sequence from various Salmonella strains is available (Parkhill et al, 2001). Salmonella spp.…”
Section: Salmonella As a Model Organism For Host-pathogen Interactionmentioning
confidence: 99%
“…Comparative genomic analysis of serotypes Typhimurium and Typhi (full genome sequences), and serotypes Dublin, Enteritidis, and Paratyphi (draft sequences) revealed that in each genome approximately 10 to 12% of unique DNA was acquired by horizontal gene transfer (96,109). Most of these acquired regions are related to the pathogenicity islands by insertion into tRNA genes (78).…”
Section: Bacterial Geneticsmentioning
confidence: 99%